Antioxidant and acetylcholinesterase inhibitory activities of Morinda citrifolia L. extracts - Sam-ang, Pornpat; Surangkul, Damratsamon; Savaspun, Kongdech; Phanumartwiwath, Anuchit (Agriculture and Natural Resources, 2020)
RESOURCESExtractions of roots, leaves and stems of Morinda citrifolia L. were carried out by maceration using ethanol, 40% ethanol/water and water, respectively. The aqueous leaf extract, ethanolic stem extract and aqueous root extract were obtained with highest percentage yields of 10.92%, 3.92% and 6.37% dry weight, respectively. The bioactivities of all the crude extracts were evaluated regarding their antioxidant and anti-acetylcholinesterase (AChE) activities. The crude ethanolic extract from roots had the relatively highest antioxidant activity with a half maximal inhibitory concentration (IC50) value of 5.97 mg/mL and total phenolic contents of 13.33 mg gallic acid equivalent/g crude extract. Moreover, the ethanolic root extract also had the most potent anti-AChE inhibitory activity with an IC50 value of 454 μg/mL. This study indicated that ethanolic M. citrifolia root extract should be a good candidate for AChE inhibitors which may be applied as herbal supplements for the prevention of Alzheimer’s disease. online